Microglial ASD-related genes are involved in oligodendrocyte differentiation - Yuta Takanezawa (Nature Portfolio, 2021)
Abstract Autism spectrum disorders (ASD) are associated with mutations of chromodomain-helicase DNA-binding protein 8 (Chd8) and tuberous sclerosis complex 2 (Tsc2). Although these ASD-related genes are detected in glial cells such as microglia, the effect of Chd8 or Tsc2 deficiency on microglial functions and microglia-mediated brain development remains unclear. In this study, we investigated the role of microglial Chd8 and Tsc2 in cytokine expression, phagocytosis activity, and neuro/gliogenesis from neural stem cells (NSCs) in vitro. Chd8 or Tsc2 knockdown in microglia reduced insulin-like growth factor-1(Igf1) expression under lipopolysaccharide (LPS) stimulation. In addition, phagocytosis activity was inhibited by Tsc2 deficiency, microglia-mediated oligodendrocyte development was inhibited, in particular, the differentiation of oligodendrocyte precursor cells to oligodendrocytes was prevented by Chd8 or Tsc2 deficiency. These results suggest that ASD-related gene expression in microglia is involved in oligodendrocyte differentiation, which may contribute to the white matter pathology relating to ASD.